The effect of differences in the third domain of the glycoprotein E of tick-borne encephalitis virus of the Far Eastern, Siberian and European subtypes on the binding of recombinant D3 proteins with a chimeric antibody - I. K. Baykov; A. L. Matveev; L. A. Emelianova; G. B. Kaverina; S. E. Tkachev; N. V. Tikunova (Вавиловский журнал генетики и селекции)
Currently, a therapeutic drug based on recombinant antibodies for the prevention and treatment of tick-borne encephalitis virus (TBEV) is developed in ICBFM SB RAS, and the chimeric antibody ch14D5 is considered as one of the key components of this drug. It was previously shown that this antibody is directed to the domain D3 of the glycoprotein E of TBEV. It was previously shown that this antibody is able to protect mice from the European subtype of TBEV, strain “Absettarov”, and the presence of virus-neutralizing activity against the Far Eastern subtype of TBEV, strain 205 was also shown for this antibody. However, it remains unclear whether this antibody exhibits selectivity for different subtypes of TBEV. The aim of this study was to investigate the effect of amino acid sequence differences of recombinant D3 domains derived from the glycoprotein E of TBEV of the Far Eastern, Siberian and European subtypes on the binding of the protective antibody ch14D5 to these proteins. Using Western blot analysis and surface plasmon resonance, it was shown that ch14D5 antibody has the highest affinity (KD= 1.7±0.5 nM) for the D3 domain of the TBEV of the “Sofjin-Ru” strain belonging to the Far Eastern subtype of the virus. At the same time, the affinity of ch14D5 antibody for similar D3 proteins derived from “Zausaev”, “1528-99” and “Absettarov” strains of the Siberian and European subtypes of TBEV was noticeably lower (KD= 25±4, 300±50, 250±50 nM, respectively). In addition, information about the spatial arrangement of amino acid residues that are different for the studied recombinant proteins indicates that the epitope recognized by the ch14D5 antibody is in close proximity to the lateral ridge of D3 domain of E glycoprotein.